2003
DOI: 10.1203/01.pdr.0000072515.10652.87
|View full text |Cite
|
Sign up to set email alerts
|

Defective Production of IL-18 and IL-12 by Cord Blood Mononuclear Cells Influences the T Helper-1 Interferon Gamma Response to Group B Streptococci

Abstract: Human neonates are uniquely susceptible to group B streptococcal (GBS) infections. We have shown that neonatal mixed mononuclear cells have a deficiency in the production of the T helper-1 (Th-1) cytokine, interferon gamma (IFN-␥), and that incubation of neonatal neutrophils with recombinant IFN-␥ corrects these neutrophil defects. IL-12 and the more recently described IL-18 are also Th-1 type cytokines that are able to induce the production of IFN-␥ in the presence of bacteria and bacterial products. We exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 31 publications
3
30
0
2
Order By: Relevance
“…Our adult kinetic studies confirmed that both cytokines were produced in large part by T and B cells (especially after PHA stimulation), and we were able to detect lymphocytic proliferation in response to GBS that was impaired in CBMC. Reduced lymphocyte IFN-␥ may reflect impaired IL-12 and IL-18 production induced by GBS (22) and, together with reduced IL-10, might suggest a bias toward Th2 responses to GBS in the newborn. IL-13 was indeed induced by GBS in our system, but the levels were relatively low and did not vary between newborns and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Our adult kinetic studies confirmed that both cytokines were produced in large part by T and B cells (especially after PHA stimulation), and we were able to detect lymphocytic proliferation in response to GBS that was impaired in CBMC. Reduced lymphocyte IFN-␥ may reflect impaired IL-12 and IL-18 production induced by GBS (22) and, together with reduced IL-10, might suggest a bias toward Th2 responses to GBS in the newborn. IL-13 was indeed induced by GBS in our system, but the levels were relatively low and did not vary between newborns and adults.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many reports indicating that the immune system is deficient in capacity to mount Th1 responses at birth (13,14) and later during infancy (21), but there have, in contrast, been only limited studies (4) on how this response capacity develops with age.…”
Section: Discussionmentioning
confidence: 99%
“…However, what is clear is that the ratio of IL-6 to TNF-␣ is higher in newborn cord blood monocytes compared with adult monocytes (7,12). Similarly, there is general agreement that production of interferon (IFN)-␥ and IL-18 in cord blood is reduced compared with adults (13,14), however, this may not necessarily apply to all cell types (15).…”
mentioning
confidence: 99%
“…It has been reported that pro-inflammatory cytokines such as tumor necrosis factor (TNF)-␣, interferon (INF)-␥, IL-1␤, IL-2, granulocyte-macrophage colony-stimulating factor (GM-CSF), and IL-15 can delay neutrophil apoptosis (24). However, some of theses cytokines, INF-␥, IL-12, and IL-18 (25) have been reported to have lower expression levels in neonatal neutrophils. This could explain why neonatal neutrophils are more susceptible to undergo apoptosis after HSV infection than adult neutrophils.…”
Section: Discussionmentioning
confidence: 99%